DNA BARCODING OF FRESHWATER FISH SPECIES OF MANNA RIVER (BENGKULU) AND SEMANKA RIVER (LAMPUNG) - Arif Wibowo; Achmad Farajalah; Husnah Husnah (Indonesian Fisheries Research Journal, 2013)
The identification of fish species is challenging. DNA barcoding provides new perspective in ecology and systematics of fishes. In this study, we assess intraspecific and interspecific genetic divergence among several freshwater fish species from Manna River of Bengkulu Province and Semanka River of Lampung Province, using data from mitochondrial cytochrome c oxidase subunit I (COI) gene. The results show that a total of six freshwater fish species identified in this study exhibited high levels of interspecific variation based on 51 analyzed sequences. Almost all species corresponded to a single species, cohesive array of barcode sequences distinct from other species. Based on Kimura Two Parameters (K2P) within species, mean pairwise sequence distances comparisons range from 0.3 to 6.3%, while interspecific comparisons were much higher range between 1.7 to 29.4%, except species Tor macrolepis and Tor putitora showed high levels of genetic similarities and no reciprocal monophyly. Using this method will obviously allow the identification eggs, larvae, fillets and fins of freshwater fish.